Effectiveness of online sexual education based on the extended PLISSIT model on sexual function and sexual satisfaction in women undergoing breast cancer treatment - Sanaz Zangeneh; Mitra Savabi-Esfahani; Fariba Taleghani; Mohammad R Sharbafchi; Mehrdad Salehi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Despite therapeutic interventions having increased the survival rate of women with breast cancer, sexual dysfunction occurs in cancer survivors due to treatment. The aim of this study is to determine the effect of online sexual education, based on the Ex-PLISSIT model on sexual function and satisfaction, on women undergoing breast cancer treatment.MATERIALS AND METHODS: The present study was a quasi-experimental and interventional control study. It was conducted with a pretest-posttest design between April and July 2022 in Isfahan, Iran. The participants were divided into an intervention (n = 40) and a control group (n = 40). The intervention group received sexual education based on the Ex-PLISSIT model that consisted of four levels of intervention, namely, permission (P), limited information (LI), specific suggestions (SS), and intensive therapy (IT), presented in four sessions. The Female Sexual Function Index (FSFI) and Larson's Sexual Satisfaction Questionnaire were used to measure the sexual function and sexual satisfaction of the participants. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 21. P values below 0.05 were considered statistically significant.RESULTS: The results showed that the mean of sexual satisfaction and function scores in the intervention group significantly increased after intervention. Moreover, the results showed a statistically significant difference in the mean of sexual satisfaction scores between the intervention and control groups after intervention (P = 0.020). Although there was a difference between the mean of sexual function scores in the intervention and control groups after the intervention, the t-test showed no statistically significant difference (P = 0.176).CONCLUSIONS: According to the results of the study, sexual education based on the Ex-PLISSIT model could effectively enhance sexual satisfaction of women undergoing breast cancer treatment. It seems that this model can help health care providers evaluate the sexual needs of the patients and provide appropriate suggestions in order to decrease sexual problems.